ANALISIS POLA PENGGUNAAN RUANG DAN WILAYAH JELAJAH BANTENG (Bos javanicus d’Alton, 1832) DI TAMAN NASIONAL ALAS PURWO JAWA TIMUR - Yanto Santosa; . Delfiandi (Media Konservasi, 2007)
Research on the pattern of bull’s spatial and homerange in Alas Ppurwo National Park, was carried out in 2 months, i.e. April-May 2006. The observation was done at four vegetation types were low-land forest, coastal forest, planted forest and grazing area. The dominant activities of bull’s on each type of vegetation were resting at lowland forest, briniy at coastal forest, and feeding at planted forest and grazing area (pasture field). Bull’s homerange in rainy season was 3,37 km2 with 21,1 km was travelled distance.Keyword: Bull, behavior, spatial use patter, home range, national park.